2018
DOI: 10.5296/ijsw.v5i1.12675
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Patients with Fall-Related Injuries in Residential Environments: Challenges for Social Work

Abstract: The study describes the osteoporosis patient's need of support from medical social workers because of risks and injury events in residential environments. The study includes qualitative interviews of patients and a survey of medical social worker visibility in the media. Findings show that patients feel a lack of knowledge, recognition, and moral respect from the environment. Support from a medical social worker is significant, and activation in a patient association and an osteoporosis school is seen as emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Research has also brought attention to the experiences of residents and family members concerning implemented home modifications (Cumming et al, 1999;Hawkins and Stewart, 2002;Petersson et al, 2009;Kruse et al, 2010;Aplin et al, 2015;Norin et al, 2017;Pettersson et al, 2017;Thodelius and Lundälv, 2018). There is also need for additional research regarding living conditions at various institutions (Thodelius et al, 2017a(Thodelius et al, , 2017bLundälv, 2018a;Lundälv, 2018b) and research has indicated a need for social support for people who have been injured (Lundälv, 2018c;Lundälv, 2018d). Previous studies have also focusing on, for example, the situations and health for elderly persons, building design for people with dementia and inclusive design of open space and safety for visually impaired persons (Leung et al, 2013;Fisher et al, 2018;Siu et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has also brought attention to the experiences of residents and family members concerning implemented home modifications (Cumming et al, 1999;Hawkins and Stewart, 2002;Petersson et al, 2009;Kruse et al, 2010;Aplin et al, 2015;Norin et al, 2017;Pettersson et al, 2017;Thodelius and Lundälv, 2018). There is also need for additional research regarding living conditions at various institutions (Thodelius et al, 2017a(Thodelius et al, , 2017bLundälv, 2018a;Lundälv, 2018b) and research has indicated a need for social support for people who have been injured (Lundälv, 2018c;Lundälv, 2018d). Previous studies have also focusing on, for example, the situations and health for elderly persons, building design for people with dementia and inclusive design of open space and safety for visually impaired persons (Leung et al, 2013;Fisher et al, 2018;Siu et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%